SAT0310 ANTI-CENTROMERE ANTIBODY ISOTYPE LEVELS AS BIOMARKER FOR DISEASE PROGRESSION IN SUBJECTS AT RISK TO DEVELOP SYSTEMIC SCLEROSIS. (2nd June 2020) - Van Leeuwen, N.; Bakker, J.; Grummels, A.; Wortel, C.; Jordan, S.; Liem, S.; Distler, O.; Hoffmann-Vold, A. M.; Melsens, K.; Smith, V.; Truchetet, M. E.; Scherer, H. U.; et al.
Abstract : Background: Presence of anti-centromere antibodies (ACA) generally associates with a better prognosis than many other systemic sclerosis (SSc) associated autoantibodies. However, presentation of the disease can be very heterogeneous and prediction of the disease course is challenging. Some older studies suggest a possible association between clinical characteristics and isotypes of ACA in patients with SSc. It is unknown whether ACA can serve as biomarker for future SSc development. Objectives: To evaluate the clinical course of very early SSc and to assess whether ACA isotype levels can identify subjects that will progress to definite SSc. Methods: ACA IgG+ patients with very early SSc (defined as presence of ACA IgG AND Raynaud and/or puffy fingers and/or abnormal nailfold capillaroscopy but not fulfilling ACR 2013 criteria) from five prospective SSc cohorts (Leiden, Zurich, Oslo, Bordeaux, Ghent) were included. Presence and levels of ACA IgG, IgM and IgA were determined at first clinical assessment and clinical course was evaluated annually. Disease progression to definite SSc, which was defined as fulfillment of the ACR 2013 criteria for SSc, and included any development of: digital ulcers (DU), interstitial lung disease (ILD) assessed by high resolution chest tomography, pulmonary arterial hypertension assessed by right heart catheterization, gastro-intestinal involvement, renal crisis or myocardial involvement was determined. ACA response characteristics were compared between very early SSc patients that progressed to definite SSc and those who did not. Logistic regression was performed to determine whether ACA response characteristics can predict progression to definite SSc, with adjustment for age and follow-up duration. Results: In total 92 subjects were included with median follow-up (FU) of 3 years (table 1 ); 39% progressed to definite SSc, mostly based on the development of skin involvement (77%). Twenty-three percent of patients developed lung involvement, 11% DU, 17% gastro-intestinal involvement and 4% myocardial involvement. Progression on more than one organ system was present in 31% of the very early SSc patients. In the multivariable logistic regression, with adjustment for age and follow-up duration, ACA IgG levels at baseline were significantly associated with progression to definite SSc (OR 3.0 (1.1-8.8)). Likewise, a trend was observed for higher ACA IgM levels (OR 1.8 (0.9-3.5)) in the very early SSc patients progressing to definite SSc (figure 1 ). Conclusion: In this study we illustrate that 39% of the ACA positive very early SSc subjects progress to definite SSc within median 4 years. We identified higher ACA IgG level as a predictive biomarker for progression to definite SSc indicating that it might be a useful biomarker for risk stratification in clinical practice. Disclosure of Interests: Nina van Leeuwen: None declared, Jaap Bakker: None declared, Annette Grummels: None declared, Corrie Wortel: None declared, Suzana Jordan: None declared, Sophie Liem: None declared, Oliver Distler Grant/research support from: Grants/Research support from Actelion, Bayer, Boehringer Ingelheim, Competitive Drug Development International Ltd. and Mitsubishi Tanabe; he also holds the issued Patent on mir-29 for the treatment of systemic sclerosis (US8247389, EP2331143)., Consultant of: Consultancy fees from Actelion, Acceleron Pharma, AnaMar, Bayer, Baecon Discovery, Blade Therapeutics, Boehringer, CSL Behring, Catenion, ChemomAb, Curzion Pharmaceuticals, Ergonex, Galapagos NV, GSK, Glenmark Pharmaceuticals, Inventiva, Italfarmaco, iQvia, medac, Medscape, Mitsubishi Tanabe Pharma, MSD, Roche, Sanofi and UCB, Speakers bureau: Speaker fees from Actelion, Bayer, Boehringer Ingelheim, Medscape, Pfizer and Roche, Anna-Maria Hoffmann-Vold Grant/research support from: Boehringer Ingelheim, Consultant of: Boehringer Ingelheim, Actelion, Bayer, GlaxoSmithKline, Speakers bureau: Boehringer Ingelheim, Actelion, Roche, Karin Melsens: None declared, Vanessa Smith Grant/research support from: The affiliated company received grants from Research Foundation - Flanders (FWO), Belgian Fund for Scientific Research in Rheumatic diseases (FWRO), Boehringer Ingelheim Pharma GmbH & Co and Janssen-Cilag NV, Consultant of: Boehringer-Ingelheim Pharma GmbH & Co, Speakers bureau: Actelion Pharmaceuticals Ltd, Boehringer-Ingelheim Pharma GmbH & Co and UCB Biopharma Sprl, Marie-Elise Truchetet: None declared, Hans Ulrich Scherer Grant/research support from: Bristol Myers Squibb, Sanofi, Pfizer, Speakers bureau: Pfizer, Lilly, Roche, Abbvie, Rene Toes: None declared, Thomas Huizinga Grant/research support from: Ablynx, Bristol-Myers Squibb, Roche, Sanofi, Consultant of: Ablynx, Bristol-Myers Squibb, Roche, Sanofi, Jeska de Vries-Bouwstra: None declared